Liquid crystal polyester resin
Patent Information
- Application Number
- JP2025058817
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0011】 本発明によれば、機械特性、ガスバリア性および成形加工性に優れた液晶ポリエステル樹脂を得ることができる。
Smart Images

Figure 2026166086000001 
Figure 2026166086000002 
Figure 2026166086000003
Abstract
Description
TECHNICAL FIELD
[0001] The present invention relates to a liquid crystalline polyester resin excellent in mechanical properties, gas barrier properties and molding processability.
BACKGROUND ART
[0002] Polyesters such as polyethylene terephthalate and polybutylene terephthalate, and liquid crystalline polyesters have excellent physical and chemical properties, and thus are widely used in various applications. Among them, liquid crystalline polyesters are excellent in mechanical properties such as rigidity, gas barrier properties, molding processability and the like, so their use is expanding not only to molded product applications but also to various applications such as fibers and films.
[0003] In recent years, from the perspective of carbon neutrality, a shift from plastics using petroleum-derived raw materials to plastics derived from renewable resources has been expected. For example, Patent Document 1 proposes a liquid crystalline polyester using, as a raw material, hydroxybenzoic acid such as vanillic acid which is a biomass-derived monomer. However, conventional liquid crystalline polyesters containing biomass-derived monomers have low flexural strength and flexural modulus, and their mechanical properties are not sufficient.
[0004] In addition, polyesters using 2,5-furandicarboxylic acid derived from renewable resources as a raw material have attracted attention, and Patent Document 2 discloses a shrink film formed using a polyester having a structural unit derived from 2,5-furandicarboxylic acid.
[0005] However, the polyester using 2,5-furandicarboxylic acid as a raw material has a low flexural modulus and inferior mechanical properties, and although the gas barrier properties are being improved, they are still not sufficient, so there is a problem that applicable uses are limited.
[0006] It has been considered difficult to satisfactorily balance the performances of mechanical properties, gas barrier properties and molding processability in polyesters using renewable resources such as 2,5-furandicarboxylic acid as raw materials. [Prior art documents] [Patent Documents]
[0007] [Patent Document 1] Japanese Patent Publication No. 2024-119149 [Patent Document 2] Japanese Patent Publication No. 2023-95930 [Overview of the Initiative] [Problems that the invention aims to solve]
[0008] The present invention aims to provide a liquid crystal polyester resin that contributes to reducing environmental impact while exhibiting excellent mechanical properties, gas barrier properties, and moldability, as well as a liquid crystal polyester resin composition containing the same, and articles made therefrom. [Means for solving the problem]
[0009] In view of the above problems, the present inventors conducted diligent studies and found that by using specific repeating units as constituent components, a liquid crystal polyester resin with excellent mechanical properties, gas barrier properties, and moldability can be obtained even when using 2,5-franzicarboxylic acid, a renewable resource, as a raw material, thus completing the present invention.
[0010] In other words, the present invention encompasses the following preferred embodiments. [1] Formula (I) ~ Formula (V) [ka] [In the formula, p, q, r, s, and t are the composition ratios (mol%) of each repeating unit in the liquid crystal polyester resin, and satisfy the following conditions: 30 ≤ p ≤ 80, 0.1 ≤ q ≤ 50, 30 ≤ p + q ≤ 86, 7≦r≦35, 0 ≤ s ≤ 35, 0.1 ≤ t ≤ 35, 7≦s+t≦35, [p+q+r+s+t≧90] Includes repeating units represented by The repeating units represented by equations (III) and (IV) are such that Ar1 and Ar2 are independent of each other, as shown in equations (1) to (4). [ka] A liquid crystal polyester resin comprising one or more repeating units selected from the group consisting of aromatic groups represented by . [2] The liquid crystal polyester resin described in [1], further satisfying p≧q. [3] The liquid crystal polyester resin according to [1] or [2], wherein the repeating unit represented by formula (III) is a repeating unit in which Ar1 is an aromatic group represented by formula (1). [4] A liquid crystal polyester resin as described in any of [1] to [3], wherein the bending strength measured in accordance with ASTM D790 using a strip-shaped test piece measuring 65 mm in length, 12.7 mm in width, and 2.0 mm in thickness is 160 MPa or more. [5] A liquid crystal polyester resin according to any of [1] to [4], wherein the flexural modulus measured in accordance with ASTM D790 using a strip-shaped test piece measuring 65 mm in length, 12.7 mm in width, and 2.0 mm in thickness is 11.1 GPa or higher. A liquid crystal polyester resin composition comprising the liquid crystal polyester resin described in any of [6], [1], to [5], and an inorganic filler and / or an organic filler. [7] The liquid crystal polyester resin composition according to [6], wherein the inorganic filler and / or organic filler is one or more selected from the group consisting of glass fiber, silica alumina fiber, alumina fiber, carbon fiber, potassium titanate fiber, aluminum borate fiber, aramid fiber, polybenzazole fiber, talc, mica, graphite, wollastonite, dolomite, clay, glass flakes, glass beads, glass balloons, calcium carbonate, barium sulfate, and titanium dioxide. An article composed of the liquid crystalline polyester resin according to any one of [8] and [1] to [5], or the liquid crystalline polyester resin composition according to [6] or [7], the article being a molded product, a film or a fiber.
Effects of the Invention
[0011] According to the present invention, a liquid crystalline polyester resin excellent in mechanical properties, gas barrier properties and molding processability can be obtained.
Modes for Carrying Out the Invention
[0012] The liquid crystalline polyester resin of the present invention (hereinafter also referred to as LCP) is a polyester or polyesteramide that forms an anisotropic molten phase, and is not particularly limited as long as it is what is referred to in the art as a thermotropic liquid crystalline polyester or a thermotropic liquid crystalline polyesteramide.
[0013] The property of the anisotropic molten phase of the liquid crystalline polyester resin can be confirmed by a conventional polarization inspection method using an orthogonal polarizer, that is, by observing a sample placed on a hot stage under a nitrogen atmosphere.
[0014] The liquid crystalline polyester resin of the present invention satisfies the formulae (I) to (V)
Chemical Formula
[0015] In terms of excellent moldability, the composition ratio p of formula (I) is 30 to 80 mol%, preferably 32 to 78 mol%, more preferably 34 to 76 mol%, even more preferably 36 to 74 mol%, and particularly preferably 38 to 72 mol%.
[0016] Specific examples of monomers that give rise to the repeating unit represented by formula (I) include, for example, 4-hydroxybenzoic acid, as well as ester-forming derivatives such as its acylids, ester derivatives, and acid halides.
[0017] In terms of excellent moldability, the composition ratio q of formula (II) is 0.1 to 50 mol%, preferably 0.5 to 48 mol%, more preferably 1 to 45 mol%, even more preferably 2 to 42 mol%, and particularly preferably 2.5 to 40 mol%.
[0018] Specific examples of monomers that give repeating units represented by formula (II) include 6-hydroxy-2-naphthoic acid, as well as ester-forming derivatives such as its acylated ester derivatives and acid halides.
[0019] p+q is 30-86 mol%, preferably 32-84 mol%, more preferably 34-82 mol%, even more preferably 36-80 mol%, and particularly preferably 38-78 mol%.
[0020] In terms of excellent mechanical properties, the composition ratio r in formula (III) is 7 to 35 mol%, preferably 8 to 32 mol%, more preferably 9 to 30 mol%, even more preferably 10 to 28 mol%, and particularly preferably 11 to 25 mol%.
[0021] Specific examples of monomers that give repeating units represented by formula (III) include hydroquinone, resorcinol, 4,4'-dihydroxybiphenyl, 2,6-dihydroxynaphthalene, and ester-forming derivatives thereof such as their acylated compounds. Hydroquinone and 4,4'-dihydroxybiphenyl are preferred in terms of their excellent mechanical properties, and hydroquinone is more preferred.
[0022] In terms of excellent mechanical properties, the composition ratio s in formula (IV) is 0 to 35 mol%, preferably 2 to 32 mol%, more preferably 4 to 30 mol%, even more preferably 6 to 28 mol%, and particularly preferably 8 to 25 mol%.
[0023] Specific examples of monomers that give repeating units represented by formula (IV) include terephthalic acid, isophthalic acid, 4,4'-biphenyldicarboxylic acid, 2,6-naphthalenedicarboxylic acid, and their ester derivatives, as well as ester-forming derivatives such as acid halides. Terephthalic acid, isophthalic acid, and 2,6-naphthalenedicarboxylic acid are preferred in terms of their excellent mechanical properties, and terephthalic acid and 2,6-naphthalenedicarboxylic acid are more preferred.
[0024] In terms of providing excellent improvements in mechanical properties and gas barrier properties, the composition ratio t in formula (V) is 0.1 to 35 mol%, preferably 0.5 to 30 mol%, more preferably 1 to 25 mol%, even more preferably 1.5 to 20 mol%, and particularly preferably 2 to 15 mol%.
[0025] Specific examples of monomers that give repeating units represented by formula (V) include 2,5-franzicarboxylic acid, as well as ester-forming derivatives thereof, acid halides, and other ester-forming derivatives.
[0026] s+t is 7 to 35 mol%, preferably 8 to 32 mol%, more preferably 9 to 30 mol%, even more preferably 10 to 28 mol%, and particularly preferably 11 to 25 mol%.
[0027] The total composition ratio of repeating units [p+q+r+s+t] in the liquid crystal polyester resin of the present invention is 90 mol% or more, preferably 92 mol% or more, more preferably 95 mol% or more, and even more preferably 98 mol% or more. The total composition ratio of repeating units [p+q+r+s+t] in the liquid crystal polyester resin of the present invention is particularly preferably 100 mol%.
[0028] Within the limits that do not impair the objective of the present invention, other repeating units may be further contained within the above composition ratio range. Examples of monomers that provide other repeating units include other aromatic hydroxycarboxylic acids, aromatic diols, aromatic dicarboxylic acids, aromatic hydroxyamines, aromatic diamines, aromatic aminocarboxylic acids, aromatic hydroxydicarboxylic acids, aliphatic diols, aliphatic dicarboxylic acids, aromatic mercaptocarboxylic acids, aromatic dithiols, aromatic mercaptophenols, and combinations thereof.
[0029] The sum of the compositional ratios of the repeating units derived from these other monomeric components is preferably 10 mol% or less in the total repeating units.
[0030] The method for producing the liquid crystal polyester resin of the present invention will be described below.
[0031] The method for producing the liquid crystal polyester resin of the present invention is not particularly limited, and known polycondensation methods for forming ester bonds with the monomer components, such as the molten acidolysis method and the slurry polymerization method, can be used.
[0032] The molten acidolysis method is a suitable method for producing the liquid crystal polyester resin of the present invention. In this method, monomers are first heated to form a molten liquid of reactants, and the reaction is continued to obtain molten polyester. Vacuum may be applied to facilitate the removal of volatile by-products (e.g., acetic acid, water, etc.) produced in the final stage of condensation.
[0033] Slurry polymerization is a method in which a reaction is carried out in the presence of a heat exchange fluid, and the solid product is obtained in a suspended state in the heat exchange medium.
[0034] In both the molten acidolysis method and the slurry polymerization method, the polymerizable monomer components used in the production of liquid crystal polyester resin can also be used in the reaction at room temperature as a modified form in which the hydroxyl group is acylated, i.e., a lower acyled. The lower acyl group preferably has 2 to 5 carbon atoms, and more preferably has 2 or 3 carbon atoms. Particularly preferred is a method in which the acetylated monomer component is used in the reaction.
[0035] The lower acylated monomers may be synthesized beforehand by acylation, or they can be generated in the reaction system during the production of liquid crystal polyester resin by adding an acylation agent such as acetic anhydride to the monomer.
[0036] In either the molten acidolysis method or the slurry polymerization method, a catalyst may be used during the reaction as needed.
[0037] Specific examples of catalysts include organotin compounds (dialkyltin oxides such as dibutyltin oxide, diaryltin oxides, etc.), titanium dioxide, antimony trioxide, organotitanium compounds (alkoxytitanium silicate, titanium alkoxide, etc.), alkali and alkaline earth metal salts of carboxylic acids (potassium acetate, sodium acetate, etc.), Lewis acids (BF3, etc.), and gaseous acid catalysts such as hydrogen halides (HCl, etc.).
[0038] The amount of catalyst used is preferably 1 to 1000 ppm relative to the monomer mass, and more preferably 2 to 200 ppm.
[0039] The liquid crystal polyester resin obtained by this polycondensation reaction is removed from the polymerization reactor in a molten state and then processed into pellets, flakes, or powder, which are then subjected to molding or melt kneading.
[0040] Liquid crystal polyester resins in pellet, flake, or powder form may be heat-treated in a substantially solid state under reduced pressure, under vacuum, or in an atmosphere of an inert gas such as nitrogen or helium, in order to increase their molecular weight and improve their heat resistance.
[0041] The heat treatment temperature is not particularly limited as long as the liquid crystal polyester resin does not melt, but is preferably 100 to 350°C, more preferably 200 to 320°C.
[0042] The liquid crystal polyester resin of the present invention preferably has a crystal melting temperature of 200 to 380°C as measured by differential scanning calorimeter, more preferably 220 to 370°C, even more preferably 260 to 360°C, and particularly preferably 290 to 350°C.
[0043] When the crystal melting temperature of liquid crystal polyester resin falls below 200°C, its heat resistance deteriorates, and when it exceeds 380°C, its moldability tends to decrease.
[0044] In this specification and in the claims, "crystal melting temperature" refers to the peak temperature of the crystal melting temperature measured by a differential scanning calorimeter (DSC) at a heating rate of 20°C / min, and is measured by the measurement method described in the examples below.
[0045] The liquid crystal polyester resin of the present invention has a flexural strength of preferably 160 MPa or higher, more preferably 165 MPa or higher, even more preferably 170 MPa or higher, and particularly preferably 175 MPa or higher, in a strip-shaped test piece measuring 65 mm in length, 12.7 mm in width, and 2.0 mm in thickness, in accordance with ASTM D790. The upper limit of the flexural strength is not particularly limited, but for example, it is 300 MPa. The flexural strength in this specification is a value measured by the measurement method described in the examples below.
[0046] The liquid crystal polyester resin of the present invention has a flexural modulus of elasticity of preferably 11.1 GPa or higher, more preferably 11.6 GPa or higher, even more preferably 12.0 GPa or higher, and particularly preferably 13.0 GPa or higher, in a strip-shaped test piece measuring 65 mm in length, 12.7 mm in width, and 2.0 mm in thickness, in accordance with ASTM D790. The upper limit of the flexural modulus is not particularly limited, but for example, it is 20.0 GPa. The flexural modulus in this specification is a value measured by the measurement method described in the examples below.
[0047] The liquid crystal polyester resin of the present invention preferably has a water vapor transmission rate of 0.20 g / m² in a 0.1 mm thick film of a molded product made therefrom, in accordance with JIS K7129-2. 2 • 24 hours or less, more preferably 0.15 g / m 2 • 24 hours or less, more preferably 0.10 g / m² 2 • 24 hours or less, particularly preferably 0.08 g / m 2 • Less than 24 hours, and typically 0.01 g / m² 2 • Indicates 24 hours or more. Note that the water vapor transmission rate in this specification is the value measured by the measurement method described in the examples below.
[0048] The liquid crystal polyester resin of the present invention obtained as described above can be a liquid crystal polyester resin composition containing inorganic fillers and / or organic fillers, additives, or other resin components.
[0049] Specific examples of inorganic and / or organic fillers that may be contained in the liquid crystal polyester resin composition of the present invention include, for example, glass fibers, silica-alumina fibers, alumina fibers, carbon fibers, potassium titanate fibers, aluminum borate fibers, aramid fibers, polybenzazole fibers, talc, mica, graphite, wollastonite, dolomite, clay, glass flakes, glass beads, glass balloons, calcium carbonate, barium sulfate, titanium dioxide, and the like. These fillers may be used alone or in combination of two or more.
[0050] If inorganic fillers and / or organic fillers are included, their content is preferably 1 to 150 parts by mass, and more preferably 10 to 100 parts by mass, per 100 parts by mass of liquid crystal polyester resin.
[0051] When the inorganic filler and / or organic filler content is 1 part by mass or more, an improvement in the mechanical properties of the liquid crystal polyester resin composition is easily obtained. When the inorganic filler and / or organic filler content exceeds 150 parts by mass, the fluidity tends to deteriorate.
[0052] Specific examples of other additives that may be contained in the liquid crystal polyester resin composition of the present invention include, for example, lubricants such as higher fatty acids, higher fatty acid esters, higher fatty acid amides, and higher fatty acid metal salts (where higher fatty acids refer to those with 10 to 25 carbon atoms), mold release agents such as polysiloxanes and fluororesins, colorants such as dyes, pigments, and carbon black, flame retardants, antistatic agents, surfactants, antioxidants such as phosphorus-based antioxidants, phenol-based antioxidants, and sulfur-based antioxidants, weathering agents, heat stabilizers, and neutralizing agents. These additives may be used individually or in combination of two or more.
[0053] When these additives are included, their content is preferably 0.01 to 10 parts by mass, and more preferably 0.1 to 3 parts by mass, based on the total amount of liquid crystal polyester resin per 100 parts by mass.
[0054] When additives are added to achieve a specific function, if their content is less than 0.01 parts by mass, the function of the additive tends to be difficult to realize, and if it exceeds 10 parts by mass, the thermal stability of the liquid crystal polyester resin composition during molding tends to deteriorate.
[0055] Furthermore, when using other additives such as lubricants and release agents, they may be added when preparing the liquid crystal polyester resin composition, or they may be attached to the surface of the liquid crystal polyester resin pellets during the molding process.
[0056] Specific examples of other resin components that may be contained in the liquid crystal polyester resin composition of the present invention include thermoplastic resins such as polyamide, polyester, polyacetal, polyphenylene ether and its modified products, polysulfone, polyethersulfone, polyetherimide, and polyamideimide, as well as thermosetting resins such as phenolic resin, epoxy resin, and polyimide resin. These resin components may be used individually or in combination of two or more.
[0057] If other resin components are included as described above, their content is preferably 0.1 to 100 parts by mass, and more preferably 0.5 to 80 parts by mass, per 100 parts by mass of liquid crystal polyester resin.
[0058] A liquid crystal polyester resin composition can be obtained by mixing a liquid crystal polyester resin with an inorganic filler and / or fillers, additives, or other resin components, and melt-kneading them using a Banbury mixer, kneader, single-screw or twin-screw extruder, etc., at a temperature ranging from near the crystal melting temperature of the liquid crystal polyester resin to the crystal melting temperature + 50°C.
[0059] The liquid crystal polyester resin or liquid crystal polyester resin composition obtained in this manner is processed into articles such as molded articles, films, or fibers by known processing methods such as injection molding, compression molding, extrusion molding, and blow molding.
[0060] The present invention will be described below with reference to examples, but the present invention is not limited in any way to the following examples. [Examples]
[0061] The crystal melting temperature, flexural strength, flexural modulus, and water vapor permeability in the examples were measured and evaluated by the method described below.
[0062] <Crystal melting temperature> Using a differential scanning calorimeter (DSC7020, Hitachi High-Tech Science Co., Ltd.), the endothermic peak temperature (Tm1) observed when the temperature was raised from room temperature at a rate of 20°C / min was recorded. The sample was then held at a temperature 20-50°C higher than Tm1 for 10 minutes. Next, the sample was cooled to room temperature at a rate of 20°C / min, and the temperature at the peak of the exothermic peak observed at this time was defined as the crystallization temperature (Tc) of the liquid crystal polymer. Furthermore, the endothermic peak was observed again when the temperature was raised at a rate of 20°C / min, and the temperature at the peak of that peak was defined as the crystallization temperature (Tm) of the liquid crystal polymer.
[0063] <Bending strength and bending modulus> Using an injection molding machine with a clamping pressure of 15t (MINIMAT M26 / 15 manufactured by Sumitomo Heavy Industries, Ltd.), the material was injected at a cylinder temperature of +10 to 30°C above the crystal melting temperature and a mold temperature of 80°C to produce strip-shaped bending test specimens (length 65mm x width 12.7mm x thickness 2.0mm). The bending test was performed using a three-point bending test with an INSTRON 5567 (universal testing machine manufactured by Instron Japan Company Limited) at a span distance of 40.0mm and a compression speed of 1.3mm / min.
[0064] <Water vapor transmission rate> A film (80mm x 80mm x 0.1mm thick) was prepared using the fusion press method, and a water vapor transmission rate test was conducted using a water vapor transmission rate measuring device (MOCON PERMATRAN-W3 / 33 MG+) in accordance with JIS K7129-2, at a temperature of 40°C and a humidity of 90%.
[0065] In the examples, the following abbreviations represent the following compounds. POB: 4-Hydroxybenzoic acid BON6: 6-hydroxy-2-naphthoic acid HQ: Hydroquinone TPA: Terephthalic acid NDA: 2,6-Naphthalenedicarboxylic acid FDCA:2,5-Franzylcarboxylic acid
[0066] [Example 1] In a reaction vessel equipped with a torque meter-equipped stirrer and distillation tube, POB, BON6, HQ, NDA, and FDCA were charged in the composition ratios shown below to a total amount of 6.5 moles. Acetic anhydride was then added at a concentration of 1.05 moles relative to the total amount of hydroxyl groups (moles) of monomers, and deacetic acid polymerization was carried out under the following conditions: The mixture was heated from room temperature to 150°C over 1 hour under a nitrogen gas atmosphere and held at that temperature for 30 minutes. Next, the mixture was rapidly heated to 210°C while distilling off the by-product acetic acid and held at that temperature for 30 minutes. Afterward, the mixture was heated to 350°C over 3 hours, and then the pressure was reduced to 20 mmHg over 30 minutes. The polymerization reaction was terminated when the predetermined torque was reached, the contents were removed from the reaction vessel, and LCP pellets were obtained using a pulverizer. The amount of acetic acid distilled during polymerization was approximately as per the theoretical value. The obtained LCP was measured and evaluated for its crystal melting temperature, flexural strength, flexural modulus, and water vapor permeability using the method described above. The results are shown in Table 1. POB: 641.9g (71.5 mol%) BON6: 30.6g (2.5 mol%) HQ: 93.0g (13 mol%) NDA: 140.5g (10 mol%) FDCA: 30.4g (3 mol%)
[0067] [Examples 2 and 3, Comparative Examples 1-3] The raw material monomers were charged to the molar percentages shown in Table 1, and LCP was obtained in the same manner as in Example 1, except that the temperature was raised to 300°C only in Example 3. Each physical property was measured for each obtained LCP. The results are shown in Table 1. Note that the crystal melting temperature could not be detected for Comparative Example 3, and molding was not possible, so it was not possible to measure each physical property.
[0068] As shown in Table 1, the liquid crystal polyester resins of Example 1 and Example 2 were comparable in balance of mechanical properties and gas barrier properties to those that did not use 2,5-franzicarboxylic acid, a renewable resource raw material (Comparative Examples 1 and 2). In fact, mechanical properties such as flexural strength and flexural modulus were improved, and gas barrier properties were also improved.
[0069] Furthermore, the liquid crystal polyester resin of Example 3 exhibited excellent mechanical properties and gas barrier properties.
[0070] [Table 1]
Claims
1. Formula (I) to formula (V) 【Chemistry 1】 [In the formula, p, q, r, s, and t are the composition ratios (mol%) of each repeating unit in the liquid crystal polyester resin, and satisfy the following conditions: 30 ≤ p ≤ 80, 0.1 ≤ q ≤ 50, 30 ≤ p + q ≤ 86, 7 ≤ r ≤ 35, 0 ≤ s ≤ 35, 0.1 ≤ t ≤ 35, 7 ≤ s + t ≤ 35, p+q+r+s+t≧90] Includes repeating units represented by The repeating units represented by formulas (III) and (IV) are Ar 1 and Ar 2 Each of these is independent of the others, and equations (1) to (4) 【Chemistry 2】 A liquid crystal polyester resin comprising one or more repeating units selected from the group consisting of aromatic groups represented by .
2. Furthermore, the liquid crystal polyester resin according to claim 1, satisfying p ≥ q.
3. The repeating unit represented by formula (III) is Ar 1 The liquid crystal polyester resin according to claim 1, wherein the repeating unit is an aromatic group represented by formula (1).
4. The liquid crystal polyester resin according to claim 1, wherein the bending strength measured in accordance with ASTM D790 using a strip-shaped test piece measuring 65 mm in length, 12.7 mm in width, and 2.0 mm in thickness is 160 MPa or more.
5. The liquid crystal polyester resin according to claim 1, wherein the flexural modulus measured in accordance with ASTM D790 using a strip-shaped test piece measuring 65 mm in length, 12.7 mm in width, and 2.0 mm in thickness is 11.1 GPa or more.
6. A liquid crystal polyester resin composition comprising the liquid crystal polyester resin described in claim 1 and an inorganic filler and / or an organic filler.
7. The liquid crystal polyester resin composition according to claim 6, wherein the inorganic filler and / or organic filler is one or more selected from the group consisting of glass fiber, silica alumina fiber, alumina fiber, carbon fiber, potassium titanate fiber, aluminum borate fiber, aramid fiber, polybenzazole fiber, talc, mica, graphite, wollastonite, dolomite, clay, glass flakes, glass beads, glass balloons, calcium carbonate, barium sulfate, and titanium dioxide.
8. An article comprising a molded article, a film, or fibers, which is made from a liquid crystal polyester resin according to any one of claims 1 to 5 or a liquid crystal polyester resin composition according to claim 6 or 7.
Citation Information
Patent Citations
Shrink film
JP2023095930A
Liquid crystalline resin and liquid crystalline resin composition, and molded article of the same
JP2024119149A